Patient Cost-Sharing and Redistribution in Health Insurance - Tobias J. Klein; Martin Salm; Suraj Upadhyay (Institute of Labor Economics (IZA), 2024)
Health insurance premiums often do not reflect individual health risks, implying redistribution from individuals with low health risks to individuals with high health risks. This paper studies whether more cost-sharing leads to less redistribution and to lower welfare of high-risk individuals. This could be the case because more cost-sharing increases out-of-pocket payments especially for high-risk individuals. We estimate a structural model of healthcare consumption using administrative data from a Dutch health insurer. We use the model to simulate the effects of a host of counterfactual policies. The policy that was in place was a 350 euro deductible. Our counterfactual experiments show that redistribution would decrease when the deductible would increase. Nonetheless, high-risk individuals can benefit from higher levels of cost-sharing. The reason is that this leads to lower premiums because both high-risk and low-risk individuals strongly react to the financial incentives cost-sharing provides.
Keywords: I13; 330; health insurance; moral hazard; patient cost-sharing; redistribution